Assessing responses and interventions to orphans and vulnerable children affected by HIV/AIDS: A case study of the experiences of HIV/AIDS orphans and vulnerable children in Gugulethu, Cape Town - Seyuba, Mesele M (Department of Social Development, 2015)
Includes abstract.